2018
DOI: 10.1093/gbe/evy036
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Facilitated Comparative Genomics of the Facultative Symbiont Hamiltonella defensa

Abstract: Many insects host facultative, bacterial symbionts that confer conditional fitness benefits to their hosts. Hamiltonella defensa is a common facultative symbiont of aphids that provides protection against parasitoid wasps. Protection levels vary among strains of H. defensa that are also differentially infected by bacteriophages named APSEs. However, little is known about trait variation among strains because only one isolate has been fully sequenced. Generating complete genomes for facultative symbionts is hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 106 publications
(180 reference statements)
1
51
1
Order By: Relevance
“…This toxin cassette encodes for a single putative virulence-associated protein with no recognisable signal peptide. Previous studies have classified the APSE-2 variant found in Hamiltonella strain ZA17 as APSE-8 (Brandt et al, 2017;Chevignon et al, 2018;Doremus and Oliver, 2017;Patel et al, 2019). However, we found that the only difference in its toxin cassette was the pseudogenisation of the first putative toxin gene within this region when compared to APSE-2 5AT and NY26.…”
Section: Apse Gene Content Variation and Toxin Cassettescontrasting
confidence: 58%
“…This toxin cassette encodes for a single putative virulence-associated protein with no recognisable signal peptide. Previous studies have classified the APSE-2 variant found in Hamiltonella strain ZA17 as APSE-8 (Brandt et al, 2017;Chevignon et al, 2018;Doremus and Oliver, 2017;Patel et al, 2019). However, we found that the only difference in its toxin cassette was the pseudogenisation of the first putative toxin gene within this region when compared to APSE-2 5AT and NY26.…”
Section: Apse Gene Content Variation and Toxin Cassettescontrasting
confidence: 58%
“…Search for genomic variants was restricted to SNPs and short insertions and deletions. The analysis of large genomic rearrangements may bring additional information on the symbiotic genomic diversity [ 67 ]. Short variant information seems to be sufficient to reconstruct symbiotic phylogenetic trees, since most phylogenetic studies rely on gene sequences analyses, and generally do not integrate rearrangements, but this structural variation should not be neglected in order to reconstruct full genomes for the main microbial genotypes existing in pea aphid holobionts.…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian inference was performed in MrBayes v3.2.5 (Ronquist et al, 2012) using the GTR+I+G AASM running two independent analyses with four chains each for 3,000,000 generations and checked for convergence. For phylogenetic inference of the Hamiltonella symbionts, we followed Chevignon et al (2018) and used the genes accD, dnaA, gyrB, hrpA, murE, ptsI, and recJ. The original authors of the aforementioned study kindly provided the alignment files, we then followed to add the newly acquired sequences and re-aligned using MUSCLE v3.8.31 (Edgar, 2004) and then removed divergent and ambiguously aligned blocks using Gblocks v0.91b.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…These Hamiltonella strains show highly syntenic reduced genomes of around 1.4 Mbp, contrasting the 2.2 Mbp genomes of the Hamiltonella defensa facultative symbionts of Ac. pisum (Chevignon et al, 2018). Based on 16S, their closes relatives are H. defensa strains ZA17, AS3, and A2C (99% identity, 2737 bit-score).…”
Section: Metabolic Complementation and The Tertiary Co-obligate Hamilmentioning
confidence: 99%
See 1 more Smart Citation